Parehong wagi at di naiiba an advocacy campaign for the rights of person with disabilities - Nery, Coco Ivana S.; Tañedo, Jose Alberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2017)
Person with disabilities, are experiencing a lot of discrimination in terms of employment, transportation and accessibility. Implementing the R.A 7277 or the Magna Carta Law have been helpful for the PWDs because stated in there are the rights of the PWDs, but are we aware of the Magna Carta Law? This advocacy campaign is dedicated to spread awareness, and to educating people about the Magna Carta Law. To change or eliminate discrimination and negative perception towards the PWDs and gain people's trust. Trust in terms of PWDs capability, because it'll help them to gain their confidence and self-esteem. To show that PWDs are not different to abled people, hence they have the same capability, and have equal rights especially in employment. Because everyone deserves to work for themselves to live. Person with disabilities, have their rights to live a normal life, all they need is acceptance from the society.
Thesis (Bachelor in Fine Arts major in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 74-75.
Keywords: People with disabilities -- Legal status, laws, etc. -- Philippines; People with disabilities